2010
DOI: 10.29079/vol9iss2art108
|View full text |Cite
|
Sign up to set email alerts
|

The histological effects of vitamin A supplement on the vaginal epithelial cells during estrus and luteal phases in Awassi sheep

Abstract: This study was carried out on the vaginal epithelium of eight Awassi ewes during estrus and luteal phases in order to evaluate the histological effect of vitamin A on the vaginal epithelium, vaginal smears were taken and stained by methylene blue. Light microscope was used in examination of slides. The present result revealed that vitamin A stimulated the process of keratinization which in turn raised the immune response of the vagina. The process of keratinization formed a sheet of strongly attached polygonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(9 reference statements)
2
0
0
Order By: Relevance
“…The herein result demonstrated that the cellular sheet formation and the intercellular communications have an important role in raising the cellular adaptive response, by obliterating the spaces between the vaginal epithelial cells to prevent the penetration of materials and invasion of pathogens between the cells and the underlying tissue. This agrees with the finding of [ 34 ] about keratinization in the vagina of ewe.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The herein result demonstrated that the cellular sheet formation and the intercellular communications have an important role in raising the cellular adaptive response, by obliterating the spaces between the vaginal epithelial cells to prevent the penetration of materials and invasion of pathogens between the cells and the underlying tissue. This agrees with the finding of [ 34 ] about keratinization in the vagina of ewe.…”
Section: Discussionsupporting
confidence: 93%
“…Endogenous bacteria metabolize the glycogen into lactic acid leading to decreasing the pH of the vagina and protecting it from pathogenic bacteria. This confirms the finding of [ 32 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%